The text of Joseph and Aseneth reconsidered - Burchard, Christoph (Journal for the study of the pseudepigrapha, 2005)
Research into Joseph and Aseneth has two forms of text at its disposal, the ‘short text’ reconstructed from one manuscript family by M. Philonenko (Joseph et Aséneth [1968], with French translation) and the ‘long text’ based on the entire evidence by C. Burchard (1979, best accessible in his Gesammelte Studien zu Joseph und Aseneth [1996]). Subsequent translators chose the short text, most interpreters preferred the long one. Recently Angelika Standhartinger (Das Frauenbild im Judentum der hellenistischen Zeit [1995]) and R.S. Kraemer (When Aseneth Met Joseph [1998]) independently of each other tried to turn the tide in favour of the short text. The present article introduces their works and attempts to show why the long text remains the better option. The last section presents new textual insights and ends with an outlook on the full-blown edition of the long text which appeared after the article was submitted to the editor (C. Burchard assisted by C. Burfeind and U.B. Fink, Joseph und Aseneth [2003]).
Keywords: Joseph et Aseneth; Textgeschichte